3(-6)+6=2(-6)

Simple and best practice solution for 3(-6)+6=2(-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-6)+6=2(-6) equation:


Simplifying
3(-6) + 6 = 2(-6)

Multiply 3 * -6
-18 + 6 = 2(-6)

Combine like terms: -18 + 6 = -12
-12 = 2(-6)

Multiply 2 * -6
-12 = -12

Add '12' to each side of the equation.
-12 + 12 = -12 + 12

Combine like terms: -12 + 12 = 0
0 = -12 + 12

Combine like terms: -12 + 12 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3p+11p=28 | | 5x-6x=8-2x | | Y=4(-5.25)+25 | | 4x+25=4 | | y/17=-11 | | 4.75=9.5-3/4x | | 9x+4=7+5x | | f/12=12/16 | | 2/3/1/13 | | Y=-3(3)+12 | | 0=9.5-3/4x | | -17/2(-20)+60 | | (a+b/c)(d-e)=f | | -17/4(-20) | | 2x-3=3x+12 | | x+0.02=870 | | 2x+16=42 | | -17/4(-20)+60 | | 2x+17=39 | | -5(2b+1)+(11b-7)=0 | | -1=5+n | | 72=3x(x+2) | | 1.3q-3.8-5.6q=-5.3q-4.3 | | 130=10x+7y | | -14=-7m | | 4+9y-3=7y+43-4y | | 729p^2-36= | | .49x^2+12x=20 | | 15+10x+x^2=0 | | -21/4(-10)+80 | | 2h+1=-17 | | -10=10a |

Equations solver categories